Neural Circuitry for Stress Information of Environmental and Internal Odor Worlds - Mori, Kensaku; Sakano, Hitoshi (Frontiers in Behavioral Neuroscience, 2022)
In mammals, odor information detected in the olfactory epithelium is converted to a topographic map of activated glomeruli in the olfactory bulb. Odor signals are then conveyed by projection neurons to the olfactory cortex for decision making. Odor information is processed by two distinct pathways, one is innate and the other is learned, which are separately activated during exhalation and inhalation, respectively. There are two types of odor signals, exteroceptive and interoceptive, which are also processed in different phases of respiration. Sensory information whether attractive/pleasant or aversive/stressful, is evaluated by the valence regions in the amygdala. Stress is an alert signal telling the body to take an action so that the normal condition can be recovered. When the odor quality is negative, the brain sets up a behavioral strategy to avoid the danger or to improve the situation. In this review article, we will describe the recent progress in the study of olfactory perception to external and internal odors.